Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1093/infdis/jiw630
|View full text |Cite
|
Sign up to set email alerts
|

CMV acquisition and inflammation in HIV-exposed uninfected Zimbabwean infants

Abstract: Cytomegalovirus (CMV) acquisition and inflammation were evaluated in 231 human immunodeficiency virus (HIV)–exposed uninfected (HEU) and 100 HIV-unexposed Zimbabwean infants aged 6 weeks. The HEU and HIV-unexposed infants had a similarly high prevalence of CMV (81.4% vs 74.0%, respectively; P = .14), but HEU infants had higher CMV loads (P = .005) and >2-fold higher C-reactive protein (CRP) concentrations (P < .0001). The CMV-positive HEU infants had higher CRP than the CMV-negative HEU infants; this associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 16 publications
(22 reference statements)
1
13
0
Order By: Relevance
“…There is a growing recognition that HEU infants have higher morbidity and mortality than HIV-unexposed infants [ 29 ], and several immune abnormalities have been described [ 31 ]. We found that HEU infants had higher levels of inflammation than HIV-unexposed infants, as reported previously [ 44 ]. Here we extend these findings by showing that CRP concentrations in HEU infants at 6 weeks were similar to levels found in HIV-infected infants, and that CRP elevation persists at 6 months of age.…”
Section: Discussionsupporting
confidence: 90%
“…There is a growing recognition that HEU infants have higher morbidity and mortality than HIV-unexposed infants [ 29 ], and several immune abnormalities have been described [ 31 ]. We found that HEU infants had higher levels of inflammation than HIV-unexposed infants, as reported previously [ 44 ]. Here we extend these findings by showing that CRP concentrations in HEU infants at 6 weeks were similar to levels found in HIV-infected infants, and that CRP elevation persists at 6 months of age.…”
Section: Discussionsupporting
confidence: 90%
“…In previous studies carried out among infants in Zimbabwe, the prevalence of CMV infection at 6 weeks of age was greater than 70%, regardless of HIV exposure, emphasizing the early acquisition of CMV infection (11,16). However, there was no report on the prevalence of maternal CMV in both studies.…”
Section: Discussionmentioning
confidence: 80%
“…HIV-exposed infants may be at higher risk of congenital CMV than HIV-unexposed infants ( 17 , 18 ). In HIV-exposed, uninfected infants, CMV infection may contribute to immune activation ( 11 , 19 , 20 ) and increase the risk of postnatal HIV infection ( 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%